Evaluation of indigofera leaf meal (Indigofera zollingeriana) on digestibility of common carp strain Sinyonya (Cyprinus carpio) - Efrizal, Riky; Hermawan, Dodi; Agung, Lukman Anugrah (Universitas Batangahari Jambi, 2025)
Common carp strain Sinyonya (Cyprinus carpio) is a freshwater fish that has high economic value. The development of fisheries cultivation business has caused an increase in demand for feed and raw materials so that feed prices become uncompetitive. Therefore, it is necessary to find alternative local feed raw materials. Plant protein source that has the potential to be developed is the indigofera (Indigofera zollingeriana) which has a protein content of 28.98‒36.62%, crude fiber 8.49‒17.40%, and fat 3.3%. This study was aimed to evaluate the use of indigofera leaf flour as a feed raw material on the digestibility of common carp. This study applied the completely randomized design experimental method containing four diet treatments and three replications, namely A (control), B (30% non-fermented indigofera leaf meal), C (30% fermented indigofera leaf meal), D (30% soybean meal). Common carp with an average body weight of 5.87±0.90 g were kept in aquariums (60 × 40 × 40 cm3) with a density of 10 fish per aquarium and fed three times a day at satiation for 30 days of maintenance. The results showed that the use of indigofera leaf flour fermented using A. niger mold had a significant effect (p<0.05) on total digestibility with a value of 53.7%, protein digestibility of 84.88% and energy digestibility of 70.60% in common carp. This study also showed that indigofera leaf flour fermented using A. niger mold could reduce crude fiber in feed from 5.21% to 2.98%.